Polymeric nanocomposites for automotive application - de Souza Neto, Francisco Nunes; Ferreira, Gabriella Ribeiro; Sequinel, Thiago; Biasotto, Glenda [UNESP]; Cruz, Sandra Andrea; Gimenez, Jessica Caroline Ferreira; Gonçalves, Roger; Scuracchio, Carlos Henrique; da Silva, Caio Marcio Paranhos; Camargo, Emerson Rodrigues; Rodrigues, Gustavo Villela; da Rosa, Cezar Augusto; et al. (Elsevier, 2022)
The large-scale synthesis of polymer-clay nanocomposites is a challenge to researchers worldwide, mainly when transforming simple materials into technological products of commercial value. It is possible to transform this challenge into an opportunity by combining simple materials into value-added products, as nanocomposites for automotive application. Factors such as increasing demand for new materials with improved properties have gained considerable attention that is expected to drive the growth of the market, which can open new opportunities to use polymer-clay nanocomposite materials for an automotive application. The transformation of polymer and clay into high-value materials is a great incentive for polymeric nanocomposites because it has a longer useful life, resistance compared to the manufacture of pristine materials, and increase in properties. This chapter provides an overview of the several synthetic methods to obtain polymer nanocomposites for automotive application. Finally, some characteristics, applications, and future aspects of polymer-clay nanocomposites are described.
Keywords: automotive application; commercial value; improved properties; Polymer-clay nanocomposites